2003
DOI: 10.3171/jns.2003.98.2.0269
|View full text |Cite
|
Sign up to set email alerts
|

Use of proton magnetic resonance spectroscopy of the brain to differentiate gliomatosis cerebri from low-grade glioma

Abstract: Owing to the unfavorable clinical outcome associated with GC compared with that associated with LGG, the findings of this study illustrate the diagnostic and prognostic value of proton MR spectroscopy in the characterization of infiltrating gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(65 citation statements)
references
References 24 publications
(19 reference statements)
4
59
0
2
Order By: Relevance
“…Extensive evidence confirms that NAA levels are lower than normal in patients with tumor or stroke (Zimmerman and Wang 1997;Taylor et al, 1998), but recent evidence shows that NAA is also reduced in traumatic brain injury (Ariza et al, 2004), multiple sclerosis (Gadea et al, 2004;Tartaglia et al, 2004), epilepsy (Bernasconi et al, 2003;Vermathen et al, 2003), vascular dementia , Alzheimer disease (Dixon et al, 2002;Valenzuela and Sachdev, 2001), Huntington disease (Sanchez-Pernaute et al, 1999), spinocerebellar ataxia (Guerrini et al, 2004), perinatal asphyxia (Pavlakis et al, 1999), transposition of the great arteries (Miller et al, 2004), mood disorder (Cecil et al, 2003), gliomatosis cerebri (Galanaud et al, 2003), focal cortical dysplasia (Vuori et al, 2004), and radiation necrosis …”
Section: Discussionmentioning
confidence: 99%
“…Extensive evidence confirms that NAA levels are lower than normal in patients with tumor or stroke (Zimmerman and Wang 1997;Taylor et al, 1998), but recent evidence shows that NAA is also reduced in traumatic brain injury (Ariza et al, 2004), multiple sclerosis (Gadea et al, 2004;Tartaglia et al, 2004), epilepsy (Bernasconi et al, 2003;Vermathen et al, 2003), vascular dementia , Alzheimer disease (Dixon et al, 2002;Valenzuela and Sachdev, 2001), Huntington disease (Sanchez-Pernaute et al, 1999), spinocerebellar ataxia (Guerrini et al, 2004), perinatal asphyxia (Pavlakis et al, 1999), transposition of the great arteries (Miller et al, 2004), mood disorder (Cecil et al, 2003), gliomatosis cerebri (Galanaud et al, 2003), focal cortical dysplasia (Vuori et al, 2004), and radiation necrosis …”
Section: Discussionmentioning
confidence: 99%
“…This hints at an increase in available Cr at an unchanged cellular energy state. Increased tCr has been assigned to reactive gliosis, which is also associated with increased MI, as shown in previous studies of different brain diseases, including MS, human immunodeficiency virus (HIV) and gliomatosis (32,(47)(48)(49)(50). Histopathology shows marked astrocytic proliferation in NAWM (51)(52)(53), which is in accordance with our findings of increased tCr and MI in normal-appearing brain tissue, and the results of others who have demonstrated that the increase in MI is not restricted to lesional tissue (10).…”
Section: Changes In Crmentioning
confidence: 99%
“…The tCr level is reduced in astrocytomas and is nearly absent in meningiomas and schwannomas, indicating changes in energy metabolism. Gliomatosis cerebri is an uncommon and infiltrative type of glioma which is difficult to diagnose but has higher levels of tCr, thus distinguishing it from low grade gliomas (Galanaud et al, 2003). The tCho/tCr ratio increases with the grade of the glioma (Gill et al, 1990) but the large overlap of ratios between grades prevents its individual use as a reliable grading index.…”
Section: Quantitative Analysis Of Glial Tumor Metabolismmentioning
confidence: 99%